Proposed percutaneous aortic valve prosthesis made of cryogel. (May 2019) - Mohammadi, Hadi; Goode, Dylan; Fradet, Guy; Mequanint, Kibret
Transcatheter heart valves are promising for high-risk patients. Generally, their leaflets are made of pericardium stented in a Nitinol basket. Despite their relative success, they are associated with significant complications such as valve migration, implantation risks, stroke, coronary obstruction, myocardial infraction, acute kidney injury (which all are due to the release of detached solid calcific pieces in to the blood stream) and expected issues existing with tissue valves such as leaflet calcification. This study is an attempt to fabricate the first ever polymeric percutaneous valves made of cryogel following the geometry and mechanical properties of porcine aortic valve to address some of the above-mentioned shortcomings. A novel, one-piece, tricuspid percutaneous valve, consisting of leaflets made entirely from the hydrogel, polyvinyl alcohol cryogel reinforced by bacterial cellulose natural nanocomposite, attached to a Nitinol basket was developed and demonstrated. Following the natural geometry of the valve, a novel approach was applied based on the revolution about an axis of a hyperboloid shape. The geometry was modified based on avoiding sharp warpage of leaflets and removal of the central opening orifice area of the valve when valve is fully closed using the finite element analysis. The modified geometry was replaced by a cloud of (control) points and was essentially converted to Bezier surfaces for further adjustment. A cavity mold was then designed and fabricated to form the valve. The fabricated valve was sewn into the Nitinol basket which is covered by Dacron cloth. The models presented in this study merit further development and revisions for both aortic and mitral positions.